Structural analysis of DNA and RNA interactions with antioxidant flavonoids. Issue 1 (2009) - Kanakis Kanakis, C. D. C. D.; Nafisi Nafisi, Sh. Sh.; Rajabi Rajabi, Mehdi Mehdi; Shadaloi Shadaloi, Azadeh Azadeh; Tarantilis Tarantilis, P. A. P. A.; Polissiou Polissiou, M. G. M. G.; Bariyanga Bariyanga, J. J.; Tajmir-Riahi Tajmir-Riahi, H. A. H. A.
Abstract : Flavonoids are natural polyphynolic compounds with major antioxidant activity that can prevent DNA damage. The anticancer and antiviral activities of these natural products are attributed to their potential biomedical applications. In this review we are examining how the antioxidant flavonoids bind DNA and RNA and what mechanism of action is involved in preventing DNA damage. Detailed spectroscopic data on the interactions of morin (mor), apigenin (api), naringin (nar), quercetin (que), kaempferol (kae) and delphinidin (del) with DNA and transfer RNA in aqueous solution at physiological conditions were analysed. The structural analysis showed flavonoids mainly intercalate into DNA and RNA duplexes with minor external binding to the major or minor groove and the backbone phosphate group with overall binding constants for DNA adducts Kmor ═5.99×10 3 M –1, Kapi ═7.10×10 4 M –1, and Knar ═3.10×10 3 M –1, Kque ═7.25×10 4 M –1, Kkae ═3.60×10 4 M –1 and Kdel ═1.66×10 4 M –1, and for tRNA adducts Kmor ═9.15×10 3 M –1, Kapi ═4.96×10 4 M –1, and Knar ═1.14×10 4 M –1, Kque ═4.80×10 4 M –1, Kkae ═4.65×10 4 M –1 and Kdel ═9.47×10 4 M –1 . The stability of adduct formation is in the order of que > api > kae > del >mor > nar for DNA and del > api > que > kae > nar > mor for tRNA. Low flavonoid concentration induces helical stabilization, whereas high pigment content causes helix opening. Flavonoids induce a partial B to A–DNA transition at high pigment concentration, while tRNA remains in A-family structure upon flavonoid complexation. The antioxidant activity of flavonoids changes in the order delphinidin > quercetin > kaempferol > morin > naringin > apigenin. The results show intercalated flavonoid molecule can act as an antioxidant and prevent DNA damage.